Toward a model to apprehend the complexity of manufacturing firm’s overall performance - Aicha Lamjahdi; Hafida Bouloiz; Maryam Gallab (International Journal of Engineering Business Management, 2020)
Recently, the company’s overall performance (OP) has become a major concern of our modern society, as a key factor that can potentially increase firm’s competitive advantage and ensure its sustainable development. However, OP is increasingly being considered as highly complex because of the complex interrelationships within industrial systems. This article presents a contribution to modeling of OP in order to apprehend its complexity and take into account the interactions between all its aspects. The proposed model is based on a combination of the value chain concept and System Modeling Language modeling. The main study established an OP indicators system to better present the firm sustainability behavior, and thus provide a comprehensive view that facilitates an in-depth understanding of its complexity. Besides, a case study from the dairy industry is presented to illustrate the model. This model can identify different activities’ interactions in the firm and understand interrelationships between OP dimensions and firm’s activities. Moreover, the proposed indicators system helps to define OP problems in the firm. Such knowledge enables managers to identify OP problems’ drivers, the related activities and set up the optimal solutions to improve the most critical activities whose performance affect the whole value chain.